Polynomials are Fun... :/

Algebra Level 4

The zeros of the polynomial : f(x) = x³ - 33x² + 354x + k

are in arithmetic progression. What is the value of k?


The answer is -1232.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Christian Daang
Oct 16, 2014

Let the zeroes of the polynomial be a-d, a, a+d respectively.

=> sum of the roots = 3a = 33 => a = 11

Next, sum of roots taken two at a time = 3a² − d² = 354 => d² = 9 => d = ±3

The roots are 8, 11, 14.

=> k = -8 * 11 * 14 = -1232

Sanjeet Raria
Oct 16, 2014

Let the roots be a d , a , a + d a-d, a, a+d .

Now applying Vieta's formula,

a d + a + a + d = 33 a-d+a+a+d=33 a = 11 \Rightarrow a=11

Also ( 11 d ) 11 + 11 ( 11 + d ) + ( 11 d ) ( 11 + d ) = 354 (11-d)11+11(11+d)+(11-d)(11+d)= 354 d 2 = 9 \Rightarrow d^2=9

Now k = 11 ( 11 d ) ( 11 + d ) k=11(11-d)(11+d)

k = 11 ( 121 d 2 ) \Rightarrow k=-11(121-d^2) = 11 ( 121 9 ) = -11(121-9) k = 1232 \huge \Rightarrow k=\boxed {-1232}

William Isoroku
Dec 2, 2014

Simple really. Since the roots are in A.P, we can express them as r d , r , r + d r-d,r,r+d . The sum is b a \frac { -b }{ a } which in this case is 33 33 .

Adding up the roots would cancel the d's (that's what she said!) and becomes: ( r d ) + r + ( r + d ) = 33 (r-d)+r+(r+d)=33 and r = 11 r=11

Now there's another useful concept of the Vieta's formula: if the roots of f ( x ) = a x 3 + b x 2 + c x + d f(x)=a{ x }^{ 3 }+b{ x }^{ 2 }+cx+d are α , β , γ \alpha ,\beta ,\gamma , then α β + β γ + α γ = b a \alpha \beta +\beta \gamma +\alpha \gamma =\frac { b }{ a }

Applying this concept, we substitute the roots: ( r ) ( 11 d ) + r ( 11 + d ) + ( 11 d ) ( 11 + d ) = 3 11 2 d 2 = 354 (r)(11-d)+r(11+d)+(11-d)(11+d)=3{ 11 }^{ 2 }-{ d }^{ 2 }=354

Solving this equation gives us d = ± 3 d=\pm 3 . It doesn't matter which 3 we use because the result will still be in A.P.

The product of the roots in an ODD-DEGREE EQUATION is the constant divide by the leading term then multiply by 1 -1 .

Substitution: ( 11 3 ) ( 11 ) ( 11 + 3 ) = k = 1232 (11-3)(11)(11+3)=-k=-1232

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...